The effect of combination of indigenous phosphate solubilizing bacteria of Riau, Indonesia on the available phosphorus and phosphorus uptake of soybean - LUFITANUR ALFIAH; DELITA ZUL; NELVIA NELVIA (Smujo International, 2018)
Alfiah L, Zul D, Nelvia N. 2018. The effect of combination of indigenous phosphate solubilizing bacteria of Riau, Indonesia on the available phosphorus and phosphorus uptake of soybean. Nusantara Bioscience 10: 146-150. Despite the abundant amount of phosphorus (P) in the soil, P uptake by the plants is very limited. In acidic soil, phosphorus (P) is bound to aluminum (Al) and iron (Fe), whereas in the alkaline soil, phosphorus (P) is bound to calcium (Ca). The improvement of efficiency and availability of P to plants can be made by utilizing a group of solubilizing phosphate microorganisms. Potency test to investigate the P solubility by Phosphate Solubilizing Bacteria (PSB) has been conducted by isolating the bacteria from peat soil at Biosphere Reserves of Giam Siak Kecil Bukit Batu, Riau, Indonesia. The semi-quantitative test revealed that the PSB were able to dissolve Ca3 (PO4)2, FePo4 and phosphate rock. However, the adaptation ability and potency of PSB from indigenous Riau peat soil inoculated into soybean (Glycine max L. Merr) plants in the mineral soil have not yet been investigated. The present study was carried out from March to June 2015 on the alluvial soil in Babussalam Village, Rambah Sub-district, Rokan Hulu District, Riau. The aim of this study was to determine the effect of PSB inoculation on bacterial population and phosphatase activity. The study also aimed to determine the available P and P uptake and their impact on soybean growth and production. The study employed a factorial experiment laid out in a completely randomized design (CRD) consisted of two factors, i.e., soil treatment and PSB. The first factor comprised of two levels, i.e., T0: non-sterilized soil, T1: sterilized soil. The second factor consisted of 4 levels, i.e., B0: without PSB inoculation, B1: inoculation using 2 isolates of PSB (BB_UB6 and BB_K9), B2: inoculation using 3 isolates of PSB (BB_UB6, BB_K9 and BB_K2), and B3: inoculation using 4 isolates of PSB (BB_UB6, BB_K9, BB_K2, and BB_HS13). The results showed that inoculation of starter 3 had the highest phosphatase activity rate of 12.43 ?g p NP g-1 hour-1. The highest available P was produced by starter 2, while the P uptake on non-sterilized soil was higher than that on the sterilized soil at 2.63 mg plant-1. PSB inoculation and soil sterilization did not significantly affect the population of phosphate solubilizing bacteria.